Online sex partner seeking and HIV testing frequency among young Black sexual minority men - Rosengren, A. Lina (J HIV AIDS Soc Serv, 2020)
Dating apps are a novel means of delivering HIV prevention messages. Young black sexual minority men (YBSMM) app users are at high risk for HIV and could benefit from frequent testing. Understanding testing behaviors among YBSMM is critical to inform tailored prevention interventions. We analyzed testing behaviors of 273 YBSMM, comparing typical testing frequency between app users and non-users using odds ratios. Overall, testing rates were high. App users were more likely than non-users to test at least every 12 months. App-using YBSMM exhibit high compliance with testing guidelines, which may indicate future successful uptake of biomedical preventions, such as Pre-Exposure Prophylaxis.